 There exists a function

Υ

(

aggregation

) conforming to the formula

Υ(

ρ

0

x

) =

ρ

1

fx

.

A pre-quasi-cartesian function can be described first defining a function

Υ

from small indexed

families of forms into forms such that

ρ

1

fx

= Υ(

ρ

0

x

)

and

x

ZC

0

fx

=

Z

1

Υ(

ρ

0

x

)

.

Definition

5.

A quasi-cartesian function is such pre-quasi-cartesian function

f

that

f

|

{

x

X

0

dom

A

|

ρ

0

x

=

A

}\

ZC

0

is an injection for every indexed family

A

of forms.

Definition 6.

A pre-quasi-cartesian function with injective aggregation is a pre-quasi-cartesian

function for which the

Υ

function is injective.

Exercise 1.

Prove that the above defined “cartesian product of an indexed family of sets” is a quasi-cartesian

function for two quasi-cartesian systems with injective aggregation.

Definition 7.

Restriction of a quasi-cartesian situation is this quasi-cartesian situation with the

set of arguments

X

replaced by a smaller set

X

such that

im

Z

X

and forms of arguments

ρ

replaced with

ρ

=

ρ

|

X

.

Proposition 8.

Every restriction of a quasi-cartesian situation is a quasi-cartesian situation.

Proof.

We need to prove

ρ

Z

ρ

=

ρ

. This formula follows from

ρ

=

ρ

|

X

and dom

ρ

im

Z

.

Definition 9.

Restriction of a pre-quasi-cartesian function is the restriction of the source quasi-

cartesian situation, the destination quasi-cartesian situation, together with a restriction of the
quasi-cartesian function to indexed families of the new set of (source) arguments.

Obvious 10.

Restriction of a pre-quasi-cartesian function is a pre-quasi-cartesian function.

Obvious 11.

Restriction of a quasi-cartesian function is a quasi-cartesian function.

Obvious 12.

Restriction of a (pre-)quasi-cartesian situation with injective aggregation is a (pre-

)quasi-cartesian situation with injective aggregation.

When card

h

f

i{

x

}

= 1

for a binary relation

f

, we will denote

f

(

x

)

or

fx

the element of the singleton

h

f

i{

x

}

.

Proposition 13.

For pre-quasi-cartesian function

f

we have

(

h

f

i{

x

X

0

dom

A

|

ρ

0

x

=

A

}

)

\ {

Z

1

f

A

)

}

=

h

f

i

(

{

x

X

0

dom

A

|

ρ

x

=

A

} \

ZC

1

)

.

Proof.

h

f

i

(

{

x

X

0

dom

A

|

ρ

0

x

=

A

} \

ZC

0

) =

h

f

i{

x

X

0

dom

A

|

ρ

0

x

=

A

x

ZC

0

}

=

h

f

i{

x

X

0

dom

A

|

ρ

0

x

=

A

fx

Z

1

Υ

f

(

ρ

0

x

)

}

=

h

f

i{

x

X

0

dom

A

|

ρ

0

x

=

A

fx

Z

1

Υ

f

A

}

=

(

h

f

i{

x

X

0

dom

A

|

ρ

0

x

=

A

}

)

\ {

Z

1

f

A

)

}

.

Proposition 14.

card

h

f

1

i{

y

}

= 1

if

y

(

h

f

i{

x

X

0

dom

A

|

ρ

0

x

=

A

}

)

\ {

Z

1

f

A

)

}

.

2